Exploring the prospect of rural tourism in Trás-os-Montes and Alto Douro (Portugal) - Pereiro, Xerardo (2018)
The de-ruralization of Portugal is a process that has dragged on since 1960 and the rural development policies have focused less on agriculture and more on tourism, and rural tourism in particular, with public investment in projects that have sought to stem the depopulation and convert functional and symbolic Portuguese rural areas. This new ruralization is for some an unsuccessful collective identity and for others a hope of positive change. In this exploratory essay I analyze the role of rural tourism in the process of de-ruralization and also new ruralization of TMAD (Trás-os-Montes and Alto Douro) from a dialogue with the existing scientific literature.